Impact of Government Economic Policies on Nigeria’s Economic Development: Economic policy, economic development, sectorial support, exchange rate and gross domestic product - Surajdeen Tunde Ajagbe; Adegoke Ahmed Aremu (Magister Akuntansi FB-UK.Maranatha, 2025)
Governments have a major impact on economic conditions through the implementation of various policies and economic intervention. This study investigates the impact of government economic policies on Nigeria's economic growth using secondary data from organizations such as the World Bank and the Central Bank of Nigeria. Utilizing a quantitative analysis approach, including multiple regression and panel time-series modeling, the findings show significant inverse relationships between real gross domestic product (RGDP) and both interest rates (INTR) and tariffs (TARR). RGDP has a significant negative correlation with INTR (-0.6749) and a moderate correlation with TARR (-0.5774). Additionally, a positive correlation exists between INTR and TARR (0.7233), as well as a moderately positive relationship between sectoral support (SECSUPP) and the exchange rate (EXR) (0.7278). The study concludes that efforts should be made to enhance beneficial effects, including advancements in technology, infrastructure, and trade policies.